The Influence of Employee Engagement and Work-Life Balance on Performance through Job Satisfaction at the Regional Development Planning Agency of Makassar City - Emilia Emilia; Muhammad Rusydi; Ahmad AC Ahmad AC (Eduvest - Journal of Universal Studies, 2024)
This study aims to determine and analyze the Effect of Employee Engagement and Work Life Balance on Job Satisfaction and Employee Performance of the Makassar City Regional Development Planning Agency. This type of research is quantitative research using questionnaires as a source of data collection, the analysis used is path analysis using the AMOS 24.0 application. The results showed that: 1. Employee engagement has a significant positive effect on job satisfaction, 2. Work-life balance has a significant positive effect on job satisfaction, 3. Employee engagement has a positive insignificant effect on employee performance, 4. Work-life balance has a significant positive effect on employee performance, 5. Job satisfaction has a significant positive effect on employee performance, 6. Employee engagement has a significant positive effect on employee performance through job satisfaction, and 7. Work-life balance has a significant positive effect on employee performance through job satisfaction.